Religionsdialog mit Anselm? Die Trinitätslehre als Stolperstein für das Gespräch zwischen Juden, Christen und Muslimen. - Ansorge, Dirk (Münchener theologische Zeitschrift, 2024)
The three Abrahamic religions -- Judaism, Christianity, and Islam -- hold a common belief in a divine being who, according to Anselm of Canterbury, is 'greater than all that can be conceived'. However, Christianity asserts that this God assumed a human nature in Jesus of Nazareth. In this context, the article refers to figures of divine revelation in Judaism and Islam, which approach the Christian concept of revelation as 'self-communication of God'. Even the concept of 'incarnation' is not foreign to Jews and Muslims. Thus, the people of Israel can be understood as the 'incarnation' of God; a similar interpretation can be applied to the 'proclamation' of the Quran in Islam. Nevertheless, both concepts do not align with the doctrinal statement of the Council of Nicaea, which asserts that the Word of God is 'coessential' with God the Father. This is why Christology and the doctrine of the Trinity represent a fundamental divergence in the discourse between monotheistic religions, which must be acknowledged despite the undisputable similarities in the concept of God.